2021
DOI: 10.1039/d1qo00783a
|View full text |Cite
|
Sign up to set email alerts
|

Chemo- and enantioselective hetero-coupling of hydroxycarbazoles catalyzed by a chiral vanadium(v) complex

Abstract: The catalytic enantioselective oxidative hetero-coupling of arenols using a chiral vanadium(v) complex has been developed. The coupling of hydroxycarbazole derivatives with various arenols provided axially chiral biarenols in high chemo-,...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 75 publications
0
24
0
Order By: Relevance
“…The intermediate can convert into radical intermediate B, which contains vanadium( iv ), via one-electron oxidation; this is because the oxidation potential of 1a is lower than that of 2a (based on cyclic voltammogram in MeCN with Bu 4 NPF 6 : E 1a (ox) = 0.45 V ( vs. Fc/Fc + ) and E 2a (ox) = 0.93 V ( vs. Fc/Fc + )). 11 Subsequently, its C–C bond formation 16 with 2a gives C. Finally, oxidation by molecular oxygen and rearomatization complete the catalytic cycle with the regeneration of V-MPS4 and/or A, releasing 3aa as the product. The formation of a vanadium( iv ) species was confirmed by electron spin resonance (ESR) analysis of V-MPS4 after performing the CDC reaction under a nitrogen atmosphere ( Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The intermediate can convert into radical intermediate B, which contains vanadium( iv ), via one-electron oxidation; this is because the oxidation potential of 1a is lower than that of 2a (based on cyclic voltammogram in MeCN with Bu 4 NPF 6 : E 1a (ox) = 0.45 V ( vs. Fc/Fc + ) and E 2a (ox) = 0.93 V ( vs. Fc/Fc + )). 11 Subsequently, its C–C bond formation 16 with 2a gives C. Finally, oxidation by molecular oxygen and rearomatization complete the catalytic cycle with the regeneration of V-MPS4 and/or A, releasing 3aa as the product. The formation of a vanadium( iv ) species was confirmed by electron spin resonance (ESR) analysis of V-MPS4 after performing the CDC reaction under a nitrogen atmosphere ( Fig.…”
Section: Resultsmentioning
confidence: 99%
“… 10 Moreover, no CDC reaction of hydroxycarbazoles mediated by heterogeneous oxovanadium catalysts has been reported so far. 11 The use of heterogeneous catalysts for this reaction would be advantageous in terms of reuse and handling. In addition, that would also be effective in avoiding unnecessary contact between the product and the catalyst to address its over-oxidation issue.…”
Section: Introductionmentioning
confidence: 99%
“…In 2021, Sasai and co-workers reported that vanadium catalysts were highly effective in cross-coupling naphthols with hydroxylcarbazole (Scheme ). This oxidative coupling through a monomeric vanadium catalyst afforded both good enantioselectivity and yield, establishing the feasibility of using vanadium catalysts in enantioselective oxidative heterocoupling reactions.…”
Section: Discussionmentioning
confidence: 99%
“…Chem. Front.2021848784885 . This paper describes the chiral vanadium complex-catalyzed oxidative heterocoupling of hydroxycarbazole for the first time.…”
Section: Key Referencesmentioning
confidence: 99%
“…A further advantage of the vanadium-catalyzed couplings is that neither a bulky substituent nor a directing group at the 3-position of 1 is required for high asymmetric induction, unlike the couplings using Cu­(II) ,,− and Fe­(III) ,, metal catalysts; however, Zhang et al, Pappo et al, and Ishihara et al developed chiral iron and copper complexes with ligands such as phosphoric acid, diphosphine oxide, and picolinic acid for the coupling reactions of 1 with no substitution at the 3-position. As numerous comprehensive reviews on the development of enantioselective oxidative coupling of 2-naphthols and their applications have been previously published, in this Account, we focus on the recent advances in oxidative couplings that used chiral vanadium complexes to afford biresorcinols, polycyclic biphenols, oxa[9]­helicenes, bi­(hydroxycarbazole)­s, ,, and C 1 -symmetrical biarenols …”
Section: Introductionmentioning
confidence: 99%